Popular understanding of democracy in contemporary China. Issue 8 (17th November 2018) - Hu, Peng
ABSTRACT: By taking the official state ideology into consideration, this article seeks to contribute to the study of public opinion of democracy under non-democratic regimes by analysing both qualitative and quantitative evidence collected in China. An examination of the ruling Chinese Communist Party (CCP)'s discourse on democracy reveals that the CCP endorses popular sovereignty and political participation while denying political contestation. Meanwhile, the concept of democracy can have three distinctive meanings among ordinary Chinese: democracy as freedom, democracy as political participation to ensure government accountability, and democracy as good socio-economic performance. Survey data show that the majority of informed Chinese respondents treat democracy as political participation to ensure government accountability, which indicates that Chinese understanding of democracy has reached to a certain degree of consensus that is closer to universally-shared idea of democracy rather than being culturally distinctive.